Analysis of e-WOM, Brand Attitude, Brand Image on Purchase Intention - Lily Purwianti; Niawati Niawati (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstrak Abstract. The purpose of this study was to analyze the positive effect of e-WOM, brand image, and brand attitude on consumer purchase intentions of online beauty products. This research was conducted on women in the city of Batam who are enthusiasts of Korean brand beauty products and are involved in e-WOM activities on Instagram social media. This study using Smart PLS version 3.0 to analyze data. The results of this test show that positive e-WOM has a significant positive effect on brand image, positive e-WOM has a positive significant effect on brand attitude, brand image has a positive significant effect on purchase intention, the brand attitude has a positive significant effect on purchase intention, e-WOM has a significant positive effect on purchase intention. Kata Kunci: brand attitude ; brand image ; e-WOM ; purchase intention